Scapular rotation in swimmers with and without impingement syndrome: Practice effects - Su, K. P.; Johnson, M. P.; Gracely, E. J.; Karduna, A. R. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The purpose of this study was to examine the effects of a normal swim practice on the scapular kinematics of swimmers with impingement syndrome and healthy swimmers. METHODS: Twenty swimmers with no known shoulder pathology and 20 swimmers with shoulder impingement syndrome participated in this study. Shoulder strength measurements were made with a hand-held dynamometer. Static scapular upward rotation was measured with an inclinometer with the arm at rest, and at 45, 90, and 135 degrees of humeral elevation. Measurements were made pre- and postswim training. RESULTS: There were no differences in baseline measurements of kinematics between the two groups. After swimming, both groups experienced muscle fatigue as indicated by a significant reduction in force generation. Although swimming practice resulted in no significant differences in scapular kinematics for the healthy swimmers, there were significant decreases in scapular upward rotation in subjects with shoulder impingement. CONCLUSIONS: Abnormal scapular kinematics in swimmers with impingement syndrome may only be observed after an intense swim practice. The examination of swimmers immediately after swimming may provide more information regarding impingement syndrome than a typical clinical exam.